Diary of Dorkius Maximus in Pompeii - Collins, Tim 1975- (Buster, 2014)
In diary format, thirteen-year-old Dorkius Maximus describes the fourth decade B.C. summer he spends with his family in Pompeii. He starts the summer believing it will be boring, but then discovers a secret that means the whole town is in terrible danger
Keywords: Geschichte 30 v. Chr.; Held; Ungeschicklichkeit; Junge; Wunsch; Tagebuch; Römisches Reich; Pompeji; Maximus, Dorkius / (Fictitious character) / Juvenile fiction; Rome / History / Juvenile fiction; Pompeii (Extinct city) / Juvenile fiction; Pompeii (Extinct city) / Fiction; Rome / History / Fiction; Family life / Fiction; Italy / Pompeii (Extinct city); Rome (Empire); Family life / Juvenile fiction; Children's stories; Diary fiction; Fiction; Historical fiction; History; Juvenile works; Kinderbuch